Hypnobirthing Effect on the Level of Pain in Labor (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Pain during labor can cause anxiety, panic and reduced ability of the uterus to contract, thereby extending time of delivery and threaten the safety of the baby. Hypnobirthing is a non-pharmacological pain management which does not have adverse effects for mother and fetus. Hypnobirthing can increase comfort, relax, reduce stress and fear during labor without loss of consciousness. The aim of this research was to determine effect of hypnobirthing on the level of pain in labor. Research was conducted in Bidan Praktik Kota Bandung. Design used was quasi experimental with One group pre and post test technique. The number of samples was 55 respondents who was given hypnosis in labor. Sampling method used was quota sampling. Data was analyzed with Mc Nemar. Result showed that there was a correlation between hypnobirthing and decreased level of pain during labor. We suggested hypnobirthing to be included in the pain management subject in the normal delivery care course and as an alternative method to reduce pain during labor.